Implementation of Marketing Strategies and Pricing to Increase Consumer Purchase Power at Makbule Outlet - Tesar Buri Anggara; Nuzulul Fatimah; Eka Fidya Priyandini (CV ODIS, 2022)
At this time, food and drink have become commonplace for the public and have even become part of life because they are normal consumption. However, this study focuses on how food and beverages obtained from abroad can attract consumers, and we conducted a study at Makbule outlets. Where the outlet sells food and beverage products, for example, sandwiches, chicken steaks, chicken katsu, and flavored teas. And how can these foods and beverages be accepted by culinary lovers who may already be used to traditional foods and drinks? This study aims to determine the influence of consumer interest in increasing purchasing power for contemporary food and how marketing strategies must be carried out so that purchasing power for these snacks can potentially be known to the public. The method in collecting data is to use a qualitative descriptive analysis method, namely by conducting interviews with buyers of Makbule outlets with the interview method, it is hoped that we can find out how consumers can get to know these foods and what reference sources are from so that they know about snacks that many audiences may not know. The conclusion can be concluded that the influence of consumer interest and purchasing power on contemporary food sandwiches, chicken steaks, and chicken katsu from Makbule outlets can be related to marketing strategies. When a good marketing strategy stimulates consumer interest in food, which is still commonplace for ordinary people.